PENGARUH WAKTU PEMBERIAN MIKRO ORGANISME LOKAL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KUBIS (Brasicca oleraceae L.) - Murdaningsih Murdaningsih (Agriculture Faculty of Flores University, 2013)
This research aims at finding out the effect of the treatment period of the local microorganism towards the growth and yield of cabbage plants (Brassica oleraceae L.) and was conducted in the experiment garden of Faculty of Agriculture Flores University in Lokoboko District, East Ndona Subdistrict, Ende Regency. The design used in this experiment is Randomized Block Design (RBD), with treatment used is M0 (without LMO treatment), M1 (once in 3 days LMO treatment), M2 (once in 5 days LMO treatment), and M3 (once in 7 days LMO treatment). The variable of the observation in this experiment is total leaves, fresh weight of crops per plant, fresh weight of crops per hectare, the diameter of the crops, fresh weight of residue, and the index of harvest. The result indicates that with the treatment of the period giving MOL 3 times a day shows the growth increase of plants’ total leaf in every period of observation 14hst, 21hst, 28hst, 35hst, 42hst). In all result variable showing the good increase to the result, M1 treatment fresh weight crop per plant is 1700 gr, fresh weight crop per ha are 68.00 tons, diameter crop is 19.52 cm, fresh weight of residue per plan are 1.94 kg, and harvest index is 46.70, M2 treatment fresh weight crop per plant is 1660 gr, fresh weight crops per ha are 1.88 kg, and harvest index are 46.89, M3 treatment fresh weight crop per plant is (1680 gr), fresh weight crop per ha are 67.2 tons, diameter crop is 18.92 cm, fresh weight residue per plant is (1,88 kg), and harvest index is 47.19.